Results of calculation and experimental studies of the functioning of the drive of an electric self-propelled machine - Oganyan E.A.; Khmelev R.N. (Научно-технический вестник Брянского государственного университета)
Wheeled electric self-propelled vehicles are increasingly being used. The paper presents the results of computational and experimental studies of the functioning of the drive of a wheeled electric self-propelled vehicle. An analysis of scientific publications in the field of electric drives of motor vehicles was carried out. It made possible to identify the current directions of their development and identify the shortcomings of existing methods. Assumptions are formulated and the main equations of the developed mathematical model are presented, based on the apparatus of connection graphs and including equations of the electromechanical subsystem and discharge of the traction battery. The developed mathematical model makes it possible to describe the functioning of the drive under consideration in both steady-state and transient modes. The results of experimental studies of the functioning of the drive of a multi-purpose electric wheeled self-propelled vehicle in steady-state and transient modes are presented. Graphs of the dependence of the current strength, the power consumed by the electric motor, as well as the torque developed by the electric motor on time under various operating conditions are shown. The adequacy of the developed mathematical description and software has been confirmed by the convergence of calculated data with experimental data obtained during testing of the author’s prototype self-propelled vehicle in real-world operating conditions.